Association Between Dairy Intake and Executive Function in Chinese Children Aged 6–12 Years - Zeng, Xia; Cai, Li; Gui, Zhaohuan; Shen, Tianran; Yang, Wenhan; Chen, Qingsong; Chen, Yajun (Frontiers in Nutrition, 2022)
Association between dairy intake and executive function remains controversial, especially among children, a population with fast-developing executive functions. This study aimed to explore this topic. Additionally, we further distinguished the role of dairy intake types (full- or low-fat, milk or yogurt) in this relationship. This survey included 5138 children aged 6-12 years. Dairy intakes were assessed by validated questionnaires. Executive function was measured by the Behavior Rating Inventory of Executive Function (Parent Version), and lower T-scores of BRIEF indices indicated superior executive function performance. Results showed that children with higher dairy intake had statistically better performance in Shift (46.58±7.48 vs 45.85±7.10), Initiate (48.02±8.58 vs 47.14±8.33), and Working Memory (50.69±8.82 vs 49.89±8.73). In the analysis of multivariate linear regression, we found that every one unit increase in full-fat dairy intake, T-scores for Shift (β=-0.350 (95% [CI]:(-0.660, -0.039) and Initiate (β=-0.486 (95% [CI]:(-0.845, -0.127) decreased, and every one unit increase in low-fat dairy intake, T-score for Organizations of Materials (β=-0.940 (95% [CI]:(-1.690, -0.189) decreased. After distinguishing dairy into milk and yogurt, we observed that only milk intake, not yogurt, significantly associated with better executive function performance in Shift (β=-0.390 (95% [CI]:(-0.745, -0.035) and Initiate (β=-0.509 (95% [CI]:(-0.917, -0.101) after adjusting for potential confounding factors. This study shows that higher intake of dairy, irrespective of fat content, is related to better executive function performance among children aged 6-12. In addition, significantly positive relationship between dairy intake and executive function’s indices of Shift and Initiate only was observed in milk, not in yogurt.